Mass-balance reconstruction for Glacier No. 354, Tien Shan, from 2003 to 2014. Issue 71 (March 2016) - Kronenberg, Marlene; Barandun, Martina; Hoelzle, Martin; Huss, Matthias; Farinotti, Daniel; Azisov, Erlan; Usubaliev, Ryskul; Gafurov, Abror; Petrakov, Dmitry; Kääb, Andreas
Abstract: This study presents a reconstruction of the seasonal mass balance of Glacier No. 354, located in the Akshiirak range, Kyrgyzstan, from 2003 to 2014. We use a distributed accumulation and temperature-index melt model driven by daily air temperature and precipitation from a nearby meteorological station. The model is calibrated with in situ measurements of the annual mass balance collected from 2011 to 2014. The snow-cover depletion pattern observed using satellite imagery provides additional information on the dynamics of mass change throughout the melting season. Two digital elevation models derived from high-resolution satellite stereo images acquired in 2003 and 2012 are used to calculate glacier volume change for the corresponding period. The geodetic mass change thus derived is used to validate the modelled cumulative glacier-wide balance. For the period 2003–12 we find a cumulative mass balance of –0.40±10mw.e.a -1 . This result agrees well with the geodetic balance of –0.48±0.07mw.e.a -1 over the same period.